The 6-min walk test in transthyretin cardiac amyloidosis: prognostic utility put to the real-world test - Poledniczek, Michael; Grubmüller, Anna; Kronberger, Christina; Willixhofer, Robin; Ermolaev, Nikita; Rettl, René; Binder, Christina; Camuz Ligios, Luciana; Eslami, Mahshid; Gregshammer, Bernhard; List, Luca; Nitsche, Christian; et al. (Frontiers in Medicine, 2025)
BackgroundThe 6-min walk test distance (6MWD) was identified as a predictor of mortality in transthyretin amyloid cardiomyopathy (ATTR-CM). However, its real-world applicability remains uncertain, as only therapy-naïve patients were included in the primary analysis.MethodsPatients from a prospective ATTR-CM registry were analyzed and included if a 6MWT was completed at baseline.ResultsA total of 252 patients [79.8 years, interquartile range (IQR): 75.4–83.7] were included. After a median of 21.7 (IQR: 12.7–34.1) months, 61 (24.2%) patients died. A 6MWD of <350 m was associated with worse survival [hazard ratio (HR): 3.29, 95% confidence interval (CI): 1.94–5.55, p < 0.001], even after adjusting for National Amyloidosis Centre stage (HR: 2.30, 95% CI: 1.29–4.10, p = 0.005). The Δ6MWD thresholds of <−35 meters/−5% were only associated with mortality after adjusting for change in treatment status.ConclusionThe 6MWD is independently associated with mortality in ATTR-CM irrespective of treatment status. A baseline 6MWD of <350 m is associated with a 3-fold risk for all-cause mortality. However, our results suggest that the Δ6MWD should only be used in patients on stable background therapy for the estimation of prognosis.